Culinary Scientists Collaborating with City Health Department and Manufacturers to Improve Public Heath: A Case from Philadelphia's Sodium Reduction in Communities Program. Issue 6 (1st November 2020) - Riordan, Molly; Zeitz, Alexandra; Fulton, Benjamin; Holliday, Darryl; Bartoli, Catherine; Aquilante, Jennifer; Spratt, Olivia; Miller, Lauren; Wilson, Anna; Deutsch, Jonathan
ABSTRACT: Philadelphia has high rates of chronic disease, including hypertension and diabetes, which can be mitigated through reduction of dietary sodium intake. To address this, the City of Philadelphia instituted nutrition standards to reduce sodium in meals served by city departments. Noting some compliant foods were hard to find, the Philadelphia Department of Public Health (PDPH) partnered with the Drexel Food Lab (DFL) to reformulate popular foods to contain less sodium. This paper details the process of sodium reduction in a Philadelphia staple, the hoagie roll, and shares the success of its implementation in over 1.6 million rolls purchased annually by the public school system.